Leakage performance of CFRP laminate under cryogenic temperature: Experimental and simulation study. (28th July 2022) - Meng, Jinxin; Zheng, Huayong; Wei, Yong; Liu, Debo; Shi, Hanqiao; Wang, Panding; Lei, Hongshuai; Fang, Daining
Abstract: Leakage rate prediction of carbon fiber reinforced polymer (CFRP) composites for cryogenic propellant tanks has been a challenge for the research community. In this paper, the leakage properties of CFRP laminates with various lay-up configurations are experimentally assessed by measuring their leakage rates under different loads and temperatures. The effects of temperature, cooling conditions and loading on the leakage rates of the above laminate composites are discussed. Meanwhile, in-situ micro X-ray computed tomography (μCT) testing is performed to characterize the internal microstructure evolution of the composites under tension. The geometric morphology and parameters of defects are investigated as well. The propagation of internal cracks in the composites under loading is carefully monitored. A novel 3D image-based model is developed using μCT scans to predict the leakage properties of the composites under various loads. The initiation and propagation leakage rates of laminates, whose values are found to be within the same order of magnitude as experimental ones. The proposed simulation method allows one to quickly calculate the image-based leakage model suitable for the prediction of leakage performance and the lay-up design of composite cryogenic propellant tanks under cryogenic temperatures. Graphical abstract: Image 1